Cuidados paliativos pediátricos: percepção da equipe multidisciplinar - Vicente, Bianca Vessecchi Talhaferro (2022)
According to the literature, Pediatric Palliative Care (PPC) advocates biopsychosocial care provided to the child and includes support for the family. Objective: To understand the perception of the multidisciplinary team about CPP. Method: Thirty-one professionals who work with hospitalized patients at the Hospital da Criança e Maternity (HCM) participated in the study. For data collection, a semi-structured interview script was used. The collected data were submitted to a qualitative analysis, in the search to understand the meanings and the perception attributed by the professionals in the PPC experience. Results: Most were female and age ranged between 23 and 53 years. Seven categories emerged: 1- Understanding about CPP; 2- Academic training; 3- Conditions eligible for Palliative Care in children: who and when; 4- Identification of the need for training; 5- Knowledge about the team that works in the institution; 6- Experiences and emotions towards the patient in CPP; 7- Dealing with your own emotions related to death. Conclusion: The present study provided a better understanding of the perception of PPCs presented by professionals. In view of the above, it is suggested the need to train health professionals and introduce the theme in the curriculum.